Client-side programming framework for building web applications - Muhammad Khairulnizam Mohd Tahir. (2009)
This project experiments with a new approach to web application development. It demonstrates this approach by implementing a web application framework. With the advent of AJAX technology, web applications no longer have the dreaded page reload effect when requesting for new data. AJAX allows data to be retrieved from the server in the background and dynamically update a portion of the page with new data thus eliminating the need for a page reload. This allows for more responsive and user-friendly experience with web applications. With more powerful JavaScript libraries, which bring rich and diverse widgets to the browser, web applications tend to become more and more like traditional desktop applications.